Hematophagy and tick-borne Rickettsial pathogen shape the microbial community structure and predicted functions within the tick vector, Amblyomma maculatum - Adegoke, Abdulsalam; Kumar, Deepak; Budachetri, Khemraj; Karim, Shahid (Frontiers in Cellular and Infection Microbiology, 2022)
Ticks are the primary vectors for emerging and resurging pathogens of public health significance worldwide. Analyzing tick bacterial composition, diversity, and functionality across developmental stages and tissues is crucial for designing new strategies to control ticks and prevent tick-borne diseases. Here, we explored the microbial communities across the developmental timeline and in different tissues of the Gulf-Coast ticks (Amblyomma maculatum). Using a high-throughput sequencing approach, the influence of blood meal and Rickettsia parkeri, a spotted fever group rickettsiae, infection in driving changes in microbiome composition, diversity, and functionality was determined. This study shows that the core microbiome of Am. maculatum comprises ten core bacterial genera. The genus Rickettsia, Francisella, and Candidatus_Midichloria are the key players, with positive interactions within each developmental stage and adult tick organ tested. Blood meal and Rickettsia parkeri led to an increase in bacterial abundance. According to functional analysis, the increase in bacterial numbers is positively correlated to highly abundant energy metabolism orthologs with blood meal. Correlation analysis identified an increase in OTUs identified as Candidatus Midichloria and a subsequent decrease in Francisella OTUs in Rickettsia parkeri infected tick stages and tissues. Results demonstrate the abundance of Rickettsia and Francisella predominate in the core microbiome of Am. maculatum, whereas Candidatus_Midichloria and Cutibacterium prevalence increase with R. parkeri-infection. Network analysis and functional annotation suggest that R. parkeri interacts positively with Candidatus_Midichloria and negatively with Francisella. We conclude that tick-transmitted pathogens, such as R. parkeri establishes infection by interacting with the core microbiome of the tick vector.